Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/mlr.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Post-discharge Follow-up Characteristics Associated With 30-Day Readmission After Heart Failure Hospitalization

Abstract: Background Readmission within 30 days after hospitalization for heart failure is a major public health problem. Objective To examine whether timing and type of post-discharge follow-up impacts risk of 30-day readmission in adults hospitalized for heart failure. Design Nested matched case-control study (January 1, 2006 to June 30, 2013). Setting A large, integrated healthcare delivery system in Northern California. Participants Hospitalized adults with a primary diagnosis of heart failure discharged to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 33 publications
1
77
0
3
Order By: Relevance
“…A PCP is a vital part in the transition of care and is someone who could easily be identified for patients to contact if they had issues with their OPAT therapy. This has already been demonstrated in oncology and heart failure patient populations …”
Section: Discussionmentioning
confidence: 70%
“…A PCP is a vital part in the transition of care and is someone who could easily be identified for patients to contact if they had issues with their OPAT therapy. This has already been demonstrated in oncology and heart failure patient populations …”
Section: Discussionmentioning
confidence: 70%
“…With over 10% of COPD patients being readmitted within 30-days, COPD is one of the leading causes of readmission in the US 6. A significant number of these readmissions are considered potentially preventable 6,12. In an attempt to reduce excessive federal health care expenditures, the ACA compels the CMS to develop a phased elimination of substantial overpayments to hospitals for patients on Medicare Advantage plans caused by preventable readmissions to hospitals for COPD (among other illnesses), a measure that will produce an estimated $132 billion in savings over the next 10 years 6,13.…”
Section: Discussionmentioning
confidence: 99%
“…It contributed to improving the c -statistics of a model based on age, gender, medications, laboratory data, and LVEF available at discharge from 0.670 to 0.710 and raised the IDI by 2.7%, which suggested that it may be helpful in predicting 30-day readmission and thus significantly improve prediction reliability when combined with other critical components. These findings may provide some help to guide follow-up strategies towards delivering optimal care, such as encouraging patients with lower KCCQ to have an early follow-up [14]. …”
Section: Discussionmentioning
confidence: 99%